Exploring Brain Death at a Tertiary Pediatric Intensive Care Unit in Turkey; Incidence, Etiology and Organ Donation - (:unkn) unknown (My University, 2016)
Amaç: Ülkemizde çocuk yoğun bakım ünitelerinde (ÇYBÜ) travmatik beyin hasarı (TBH) sonrası beyin ölümü sıklığı bilinmemektedir. Amacımız ÇYBÜ'müzde beyin ölümü ve organ bağışı oranlarımızı saptamak, beyin ölümü gerçekleşen hastaların demografik, etiyolojik ve tanımlayıcı ek bilgilerini paylaşmaktır. Yöntemler: Mart 2012 ve Aralık 2014 tarihleri arasında üçüncü basamak ÇYBÜ'de saptanan tüm beyin ölümü olguları beyin ölümü veritabanımızdan, bu tarihler arası yatırılan tüm hasta sayısı ve yatış etiyolojisi tıbbi (elektronik ve dosya) kayıtlardan elde edildi. Bulgular: ÇYBÜ'ye yatırılan 889 hastadan 63 tanesi travma nedeniyle yatmış olup 33 tanesinde ağır TBH mevcuttu. Beyin ölümü 10 çocukta saptanmıştı. Kaba beyin ölümü oranı %1,1 olarak hesaplandı. Beyin ölümü saptanan hastaların %70'inde ağır TBH mevcuttu. Bu hastaların ortalama yaş ve ağırlıkları 7,2 (±3,2) yıl ve 25,7 (±9,6) kilogram idi. Ağır TBH olan hastalarda ölümün en sık nedenini beyin ölümünün gerçekleşmesi oluşturuyordu (%53). İki hasta organ vericisi oldu (%20). Sonuç: ÇYBÜ'müzde beyin ölümü olgularının çoğunu ağır TBH olanlar oluşturmaktadır. ÇYBÜ beyin ölümü olgularının insidansı ve etiyolojilerinin bilinmesinin farkındalığı arttırarak beyin ölümü tanısını hızlandıracağını, organ bağış oranlarına katkı sağlayacağını düşünmekteyiz.

Introduction: Severe traumatic brain injury (TBI) is associated with brain death. The overall incidence of pediatric brain death, especially in severe TBI is not known in Turkey. We aimed to investigate the rate of brain death determinations and organ donations in our tertiary pediatric intensive care unit (PICU), and to report the data on demographic pattern and supplementary descriptive data on the brain death declarations.Methods: We retrospectively evaluated all children who were declared brain-dead in our tertiary PICU between March 2012 and December 2014. Pertinent data was obtained from hospital medical records (electronic and chart) and brain death database of the unit.Results: Out of 889 patients, 63 were admitted to the PICU due to trauma in general and 33 had severe TBI. There were 10 brain death declarations, and only 3 were in critically ill children due to non-traumatic causes. The crude incidence of brain death was 1.1% in our patient population. 70% of brain death declarations were due to severe TBI. The mean age and weight of the patients, who were declared brain dead, were 7.2 (±3.2) years and 25.7 (±9.6) kilograms, respectively. In 13 patients, who died due to severe TBI, brain death was the most common mode of death (53%). Two patients became organ donors (20%).Conclusion: Brain death is a common mode of death after severe TBI, more frequent than non-trauma cases admitted to our PICU. Awareness of the incidence and etiology may contribute to timely diagnosis and declarations, and increased organ donation
Ülkemizde Üçüncü Basamak Bir Çocuk Yoğun Bakım Ünitesindeki Beyin Ölümlerinin İncelenmesi; İnsidans, Etiyoloji ve Organ Bağışı
Keywords: Acil Tıp; Pediatri